Calcium sulfate matrix as local antibiotic carrier in the mastoid. Issue 3 (10th March 2022) - Dalbert, Adrian; Bächinger, David; Soyka, Michael; Röösli, Christof; Inci, Ilhan; Schuurmans, Macé M.; Achermann, Yvonne; Huber, Alexander
Abstract: We describe the use of calcium sulfate beads as antibiotic carrier in a patient, who suffered from chronic mastoiditis with consecutive otogenic meningitis due to Burkholderia cenocepacia. Our findings suggest a possible role of calcium sulfate matrix as a local antibiotic carrier in the mastoid in complicated mastoiditis cases. Abstract : Calcium sulfate matrix as local antibiotic carrier could be a useful adjunct in complicated mastoiditis cases or infections after otologic surgeries involving foreign body material.